Suspended nanoparticles on mixed convection flow of a Jeffrey fluid due to a horizontal circular cylinder with viscous dissipation - Syazwani, Mohd Zokri; Nur Syamilah, Arifin; Abdul Rahman, Mohd Kasim; Mohd Zuki, Salleh (VINČA Institute of Nuclear Sciences, 2020)
The non-Newtonian Jeffrey fluid model describes the viscoelastic property that elucidates the dual components of relaxation and retardation times. Nonetheless, there has been considerable attention on its unsatisfactory thermal performance. The model of nanofluid is contemporarily in the limelight due to its superior thermal performance compared to the conventional fluid. The proposed study herein aims to examine the Jeffrey nanofluid model over a horizontal circular cylinder with mixed convection flow. The flow analysis is performed based on the Buongiorno model with the integration of Brownian motion and thermophoresis diffusion parameters. The influence of frictional heat is also accounted. The non-dimensional and non-similarity transformation variables are utilized to reduce the dimensional governing equations into three non-dimensional PDE. Subsequently, the obtained PDE are tackled numerically through the Keller-box method. Certain continent parameters are investigated with regards to the identified distributions. A comparative study is executed based on previous studies, which indicates good agreement with results of the current study. The findings specify that the transition of boundary-layer from laminar to turbulent flows happens for dissimilar values of mixed convection parameter, Deborah number, Brownian motion and Eckert number. In particular, the boundary-layer separates from cylinder for positive (heated cylinder) and negative (cooled cylinder) values of mixed convection parameter. Heating the cylinder defers the separation of boundary-layer, while cooling the cylinder carries the separation point close to the lower stagnation point.